Chemical Constituents And Cytotoxocity Of The Stem Bark Calophyllum Lanigerum Var. Austrocoriaceum (Whitemore) P. F. Stevens And Calophyllum Andersonii P. F. Stevens - Mokhtar, Norisha (2024)
Plants from the genus Calophyllum, have gained the interest of phytochemists due to the exciting new discoveries of its bioactive constituents. Phytoconstituents such as coumarins, chromanones, xanthones, and triterpenoids are frequently discovered phytochemical groups in this genus. These phytochemicals proven to possess potential pharmacological importance that are essential for scientists to subject it in pharmacotherapeutic applications in treating targeted diseases. For example, used for pharmacotherapeutic purpose in treating HIV, cancer, and inflammatory related diseases. In this study, the stem bark of Calophyllum lanigerum and Calophyllum andersonii were investigated by extracting, isolating, and characterising the possible phytochemicals that present and assessing their cytotoxic activity, respectively. Five phenolics and two triterpenoids have been isolated from the stem bark of C. lanigerum. The phenolic compounds were identified as caloteysmannic acid (A), isocalolongic acid (B), calolongic acid (C), euxanthone (D), calanone (E), and two common triterpenoids, friedelin (F) and stigmasterol (G). Meanwhile, calanone (E) and its constitutional isomer, isocalanone (H) together with soulattrolide (I) and friedelin (F) were isolated from the stem bark of C. andersonii. Chromanone acids (Compounds A and B) were reported for the first time in C. lanigerum in Sarawak region. The chemical structures of these isolated compounds were elucidated using detailed spectroscopic techniques including NMR (1D, 2D), MS, UV-Vis, FTIR. Extracts (n- xxi hexane, chloroform, ethyl acetate) and compounds (A, B, E, and H) from both Calophyllum species were subjected for their cytotoxicity against HeLa Chang liver (human cervix carcinoma) and HL-7702 (human normal liver) cell lines. Only ethyl acetate extract from C. lanigerum exhibited promising cytotoxicity, with IC50 value of 34.13 ± 3.82 μg/mL, while n-hexane and chloroform extracts showed moderate cytotoxicity against Hela Chang liver cell line [IC50: 93.84 ± 9.35 μg/mL and 81.33 ± 2.41 μg/mL, respectively]. The observed cytotoxic effects of the ethyl acetate extract suggest its potential for further development as an anticancer agent.